Laplacian Operators for Scientific Computing: A Comparative Analysis of CPU and GPU Implementations - J, Aswini; Richee J, Marinto; Dinesh, M. G.; Gayathri, A. (Journal of Neonatal Surgery, 2025)
This paper presents a comprehensive bench-marking study of a 2D Laplacian filter implemented on both CPU and GPU architectures for image processing applications. The Laplacian filter serves as a fundamental tool in edge detection and feature extraction, playing a crucial role in various computer vision tasks